2021
DOI: 10.2147/ijgm.s343644
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Higher Cumulative Dose of Cisplatin for Concurrent Chemoradiation and Acute Kidney Disease Incidence Among Nasopharyngeal Carcinoma Patients: A Comparative Study

Abstract: Introduction Nasopharyngeal carcinoma (NPC) is the most malignant cancer in the head and neck area. According to the stage, the management of NPC includes radiation, chemotherapy, or a combination of both. The standard agent for radiosensitizing chemotherapy is cisplatin. Among the several effects of cisplatin administration, nephrotoxicity raises the most concern, especially in high doses. Acute kidney disease (AKD) is a condition in which an acute kidney injury occurs at >7 days but <90 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In recent years, the immunotherapy dominated by PD-1/PD-L1 immune checkpoint inhibitors has been gradually applied to the comprehensive treatment regimen for various types of tumors. Camrelizumab is the third PD-1 drug made in China after toripalimab and sintilimab and can activate T cells by blocking PD-1/PD-L1 binding, thereby weakening the immunosuppression within the patients' organism and enhancing the tumor-killing effect [ 7 , 8 ]. Zhou et al gave the patients with advanced nasopharyngeal carcinoma targeted therapy combined with immunotherapy (anrotinib + camrelizumab), and the patients' recheck showed that they had shrunken lesions, significantly relieved cough and active shortness of breath, and remarkably improved quality of life [ 9 ], suggesting that anrotinib + camrelizumab has treatment effect on the patients with nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the immunotherapy dominated by PD-1/PD-L1 immune checkpoint inhibitors has been gradually applied to the comprehensive treatment regimen for various types of tumors. Camrelizumab is the third PD-1 drug made in China after toripalimab and sintilimab and can activate T cells by blocking PD-1/PD-L1 binding, thereby weakening the immunosuppression within the patients' organism and enhancing the tumor-killing effect [ 7 , 8 ]. Zhou et al gave the patients with advanced nasopharyngeal carcinoma targeted therapy combined with immunotherapy (anrotinib + camrelizumab), and the patients' recheck showed that they had shrunken lesions, significantly relieved cough and active shortness of breath, and remarkably improved quality of life [ 9 ], suggesting that anrotinib + camrelizumab has treatment effect on the patients with nasopharyngeal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…We retrospectively analyzed the courses of all patients treated with cisplatin-based EXTREME regimen for various head and neck tumors at our hospital center between June 2009 and July 2022. We considered that each as independent, given that the cumulative dose did not appear to influence the risk of AKI [ 43 ], that patient management was similar between each course and that the regimen timeframe was short for each patient (negligible effect of age on kidney function).…”
Section: Methodsmentioning
confidence: 99%
“…A review of patients’ charts to ascertain the cumulative exposure to chemo- and immunotherapeutic agents and other medications is important to assess the risk of nephrotoxicity and other less common therapy-associated injuries (e.g., thrombotic microangiopathy, tubulointerstitial nephritis, glomerular diseases, and intratubular obstruction from medications) must also be considered [ 44 ]. Notably, the risk of nephrotoxicity increases from cumulative exposure to chemotherapeutic agents and other medications [ 194 , 195 ]. The risk of AKI increases with the number of nephrotoxic drugs used, and all potentially nephrotoxic agents that can be stopped should be discontinued [ 146 , 196 ].…”
Section: Managementmentioning
confidence: 99%